The Evaluation of Model School Programs at SMPN 4 Padang west Sumatera Province - Irawati Irawati; Ambiyar Ambiyar; Fahmi Rizal; Fetri Yeni J (International Journal of Educational Dynamics, 2020)
The aims of this research to evaluate the Model School Program Padang Public Junior High School 4 which can provide accurate information for the central government, local governments, school principals, teachers, and other interested parties, and is optimally beneficial for the implementation of the Model School Program. This type of research is a research evaluation with a quantitative descriptive approach. The evaluation model used is the CIPPO model (context, input, process, product, outcome) developed by Stufflebeam. Data collection techniques are carried out using observation, questionnaires, and documentation. The subjects of this study were the School Education Quality Assurance Team (TPMPS) Model Padang Public Junior High School 4 and schools scanning: Padang Public Junior High School 3 and Padang Frater Junior High School. The results showed that the Model School and scaling Program at Padang Public Junior High School 4 had been well implemented and must continue so that schools can implement education quality assurance independently and form schools with quality culture. The CIPPO evaluation is used to optimize problems that occur in the implementation of the Model School Program and its impact on schools scanning of Padang Public Junior High School 3 and Padang Frater Junior High School.